IMPLEMENTASI TOTAL QUALITY MANAGEMENT (TQM) AT MADRASAH - Iwan Setiawan; Anis Zohriah (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2023)
The implementation of Total Quality Management (TQM) in madrasas aims to improve the quality of education as a whole. TQM provides the concept that quality is the responsibility of all parties involved in the educational process. This study aims to determine the implementation of TQM in Madrasah Aliyah (MA) and the factors that influence it. This study uses a qualitative approach with data collection techniques through in-depth interviews, observation, and documentation studies. The results of the study show that the implementation of TQM in MA has been going well and has affected the improvement of the quality of education. Factors influencing the implementation of TQM include support from school principals, active participation of all relevant parties, effective measurement and evaluation systems, and implementation of staff training and development. This study recommends the need for increased awareness and active participation of all parties involved in the implementation of TQM and the need for continuous development and training for madrasah staff.